Pathogenic bacteria (Henry Stewart Talks, 2026)
Nature of pathogenic bacteria, Virulence factors, Clinical syndromes, Routes of transmission, Diagnosis and treatment, Antibiotic resistance, Control of bacterial spread, Vaccination and infection control, Public health measures